Pandangan Karyawan tentang Dukungan Organisasi: Penguatan Komitmen Organisasi atau Turnover Intention? - Rahayu Mardikaningsih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Organizations need to retain employees who have high work results and productivity at work because these efforts will affect the operational efficiency of the organization. Employee commitment needs careful scrutiny for resource development programs to have high equity value in the future. However, many organizations have turnover intention problems. The existence of turnover intention is considered to have a bad quality on the relationship between parties. Dissatisfied workers are one of the causes and employees may have the impression that there is no organizational support so that workers' interests are met regarding task completion. This study was conducted with the intention of analysing and determining the relationship between perceived organizational support with commitment and turnover intention. Using a correlational approach survey method, the survey consisted of 72 employees as the survey sample. The findings of the study suggest that there is a strong positive correlation between organizational support and commitment but with turnover intention, the negative relationship is quite weak. This has been proven by the correlation test. The better the employees' impression of organizational support, the more their commitment increases and the less likely they are to move. Conversely, the lower the impression of organizational support for employees, the lower the commitment and the greater the turnover intention.